2020
DOI: 10.1111/codi.15235
|View full text |Cite
|
Sign up to set email alerts
|

Predicting outcomes of pelvic exenteration using machine learning

Abstract: Aim We aim to compare machine learning with neural network performance in predicting R0 resection (R0), length of stay > 14 days (LOS), major complication rates at 30 days postoperatively (COMP) and survival greater than 1 year (SURV) for patients having pelvic exenteration for locally advanced and recurrent rectal cancer. Method A deep learning computer was built and the programming environment was established. The PelvEx Collaborative database was used which contains anonymized data on patients who underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…Consistent with this, we noted an association between operative time and postoperative complications which is likely representative of the more complex surgical resections predisposing patients to major complications [ 27 ]. A large study from the PelvEx collaborative similarly identified prolonged operative time as negatively associated with 30-day complications [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, we noted an association between operative time and postoperative complications which is likely representative of the more complex surgical resections predisposing patients to major complications [ 27 ]. A large study from the PelvEx collaborative similarly identified prolonged operative time as negatively associated with 30-day complications [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are several studied that have investigated the predictive value of 18 F -FDG PET-CT in the LARC and in recurrent rectal cancer, and more are likely to be produced using collaborative, international research platforms [18][19][20][21][22][23][24][25][26][27]. However, these studies have some limits mainly due to the methodological heterogeneity secondary to their multicentric nature in terms of preoperative studies, chemoradiotherapy, patients' characteristics and PET study method (timing, technique and analysis of images).…”
Section: Discussionmentioning
confidence: 99%
“…The application of ML algorithms resulted in a moderate ability to predict outcomes of pelvic exenteration surgery, even by using more complex ANNs [23].…”
Section: Random Forest Algorithms Have Been Used Bymentioning
confidence: 99%
“…The PelvEx group trained ML models and ANNs to predict LOS with modest to moderate predictive ability [23]. Jo et al [63] developed an algorithm with ML that performed well for colon cancer (AUC 0.71).…”
Section: Oncologic Outcomesmentioning
confidence: 99%